A comparative, cross-cultural criminal career analysis. (July 2015) - Rocque, Michael; Posick, Chad; Marshall, Ineke Haen; Piquero, Alex R
For over 30 years, the criminal career paradigm in criminology has raised important theoretical and policy questions as well as research on the 'dimensions' of the criminal career (for example, onset, duration, lambda, persistence, chronicity, desistance). Yet few studies have examined criminal career dimensions using a cross-national comparative approach. In this paper, we use an international sample of students (aged 12–15 years) from 30 countries (International Self-Report Delinquency Study-2): (1) to determine the extent of cross-national variation in the prevalence and correlates of high-frequency, serious offenders; and (2) to explore cross-national variation in offending patterns and selected correlates of offense specialization (for example, gender, self-control, delinquent peer association). Although we find several factors are correlated with criminal career dimensions across context, important differences emerged as well that have implications for developing context-specific theories of crime and effective offender programming.